Storage of Instant Dhal in Different Packaging Films under Ambient Conditions - Nayak, L; Samuel, DVK; Pandey, H (Journal of Agricultural Engineering, 2004)
Instant dhal was prepared by soaking the split dhal in sodium carbonate (Na2CO3), followed with cooking, drying, flaking and drying. The prepared dhal was then stored at ambient temperature (25 ± 1degree C) in three different packaging materials (Polyethylene, polypropylene and polyester-aluminum- polyethylene laminate) for a period of 105 days. The quality of the stored food product was determined by measuring the peroxide value (PV), thiobarbituric acid (TBA), free fatty acid (FFA) values and conducting sensory evaluation for colour, odour, taste and overall acceptability. PFP laminate was found to be best as compared to other two packaging materials with sensory score of 6.75, 6.15, 5.75 and 6.37 for colour, odour, taste and overall acceptability after 105 days of storage. Also the PV, TBA and FFA values were 85, 0.52, 4.86, respectively after storage of the product in PFP laminate, which were best as compared to other packaging material.